OP0100 Overall cancer risk in patients with rheumatoid arthritis treated with tnf inhibitors, tocilizumab, abatacept, or rituximab. (15th June 2017) - Wadström, H; Frisell, T; Askling, J
Abstract : Background: Immune incompetence may lower host surveillance against incipient tumours. Conversely, immune therapies have emerged as a promising therapeutic approach to cancer. Malignancies thus constitute an important aspect of the safety of biologics as used in Rheumatology, including agents targeting TNF, CD20 and IL6, and immunomodulation using CTLA4. Whereas previous reports concerning TNF inhibitors (TNFi) and risk of malignancies in rheumatoid arthritis (RA) have mostly been reassuring, risks with other biological disease modifying anti-rheumatic drugs (bDMARDs) are less studied. Objectives: To assess the risk of malignancies in patients with RA treated with bDMARDs. Methods: Through linkages of Swedish national and population-based registers we assembled cohorts of patients with RA initiating (Jan 2006 through Dec 2014) a first ever treatment of tocilizumab, abatacept, rituximab, or a TNFi, one cohort of patients initiating a second TNFi, one cohort of biologics-naïve csDMARD treated RA. Through linkage with the Swedish Cancer Register information on incident cancers was collected. Outcomes were defined as a first ever solid or hematologic malignancy excluding non-melanoma skin cancer (NMSC) during follow-up. Patients with a previous malignancy were excluded. Patients were followed from treatment start until death, emigration, outcome or end of follow up (Dec 2014). Hazard ratios were calculated using Cox-regression adjusted for age, sex, educational level, comorbidities, sero-positivity, number of hospitalizations and days spent in inpatient care, use of prednisolone at baseline, use of non-steroidal anti-inflammatory drugs (NSAIDs) at baseline, number of prescription drugs at baseline, and sick leave and disability (yes/no) the year before cohort entry. Results: Adjusted for age, sex, disease- and treatment characteristics (see above), and educational level, there were no statistically significant differences in risk of a first solid or hematologic malignancy between initiators of tocilizumab, abatacept, rituximab, or a first- or second TNFi, and RA patients treated with csDMARDs. Conclusions: The overall risk of malignancies among RA patients initiating, tocilizumab, abatacept, rituximab, or a first- or second TNFi in clinical practice did not differ substantially from that of RA patients treated with csDMARDs. Increased risk of tumours at specific sites, or with longer latency, cannot be excluded. Disclosure of Interest: None declared